EDITORIAL :DISSECTING THE MOLECULAR MECHANISMS OF INTESTINAL BACTERIAL TRANSLOCATION TO FACILITATE DEFINITION OF ITS PROPOSED ROLE IN SYSTEMIC SEPSIS (Iraqi Journal of Medical Sciences, 2016)
Intestinal translocation of bacteria is de?ned as the ingress of gastrointestinal micro?ora across the lamina propria to local mesenteric lymph nodes and thence to extranodal sites. Bacterial translocation has been long been considered as a possible direct cause of sepsis when under certain conditions bacteria cross the intestinal barrier, enter the systemic circulation and cause ageneralised inflammatory response syndrome. While this is an attractive hypothesis, which finds support from experimental models, evidence from clinical studies is equivocal in confirming that bacterial translocation is the primary cause of sepsis. Moreover, the underlying mechanisms by which gut bacteria gain entry to the systemic circulation are not well defined. This review provides a brief overview of bacterial translocation in the intestine, discusses our current understanding of the role it plays in the development of sepsis syndrome and suggests areas for future research to determine the molecular mechanism(s) involved in the aetiology of disease.Keywords: Bacterial translocation; mesenteric lymph node; gastrointestinal micro?ora; enteric bacteria; sepsis
Keywords: Bacterial translocation mesenteric lymph node gastrointestinal microora enteric bacteria sepsis